The Effect of Traditional Folk Games During the Independence Day Celebration on the Development of Gross Motor Skills in Elementary School Children - Agnes Monica Hutahaean; Rifaldo P. Simbolon; Dedi Torman Gea; Nurfadillah Siregar (Journal of Foundational Learning and Child Development, 2025)
Purpose of the study: This research investigated the effect of traditional Indonesian folk games practiced during Independence Day celebrations on the development of gross motor skills in elementary school children. Traditional games represent a culturally relevant and engaging approach to physical education that may enhance fundamental motor development in school-aged children. Materials and methods: A quasi-experimental pretest-posttest control group design was employed with 40 students (20 boys and 20 girls) aged 9–11 years from Sekolah Dasar Negeri 106809 Kolam, Indonesia. Participants were divided into experimental (n=20) and control (n=20) groups using purposive sampling. The experimental group participated in a four-week traditional folk games intervention (three 60-minute sessions per week) featuring balap karung (sack race), tarik tambang (tug of war), gobak sodor, and engklek. The control group continued regular physical education curriculum. Gross motor skills were assessed using the Test of Gross Motor Development–Third Edition (TGMD-3) at baseline and post-intervention. Data were analyzed using paired t-tests for within-group changes and independent t-tests for between-group comparisons (p < 0.05). Results: The experimental group demonstrated significant improvements in both locomotor skills (pre: 38.45±4.12 vs. post: 43.80±3.85, p < 0.001, d = 1.34) and object control skills (pre: 41.30±5.28 vs. post: 47.15±4.62, p < 0.001, d = 1.20), with a total TGMD-3 score increase from 79.75±8.84 to 90.95±7.89 (p < 0.001, d = 1.33). The control group showed minimal changes (p > 0.05). Between-group analysis revealed significant differences favoring the experimental group in locomotor skills (p < 0.001, d = 1.89), object control skills (p < 0.001, d = 1.62), and total scores (p < 0.001, d = 1.85). Conclusions: Traditional folk games conducted during Independence Day celebrations significantly enhanced gross motor skill development in elementary school children. These culturally relevant activities provide an effective, engaging, and contextually appropriate intervention for promoting fundamental motor skills. Physical educators and school administrators should consider incorporating traditional games into physical education curricula as an evidence-based strategy for motor development.